Age, Gender, and Anxiety as Antecedents of Willingness to Communicate: Turkish EFL Context - Yetkin, Ramazan; ÖZER, Zekiye (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2022)
Individual differences in language learning have been under close scrutiny for several decades. However, there seems to be research ground to be filled in with new research to understand how and to what extent these differences relate to/affect the language learning process. Foreign language classroom anxiety (FLCA) and second language willingness to communicate (L2 WTC) have been key individual differences in research paradigms in educational psychology and applied linguistics. To this end, the current study aims to disclose secondary school EFL learners’ FLCA/ L2 WTC levels and their relations and predictions by comparing and relating participants’ age and gender differences. The participants were 131 secondary school students in the English as a foreign language (EFL) context. Statistical results pointed out moderate levels of FLCA and WTC among participants. When age and gender differences were compared, it was observed that both of the variables made a significant difference in participants' FLCA and WTC scores with females surpassing males in their mean values. Also, regression analysis indicated age and gender as the significant predictors of WTC. It is clear from the study results that both age and gender are significant factors intervening in the language learning process. Teachers should be aware of these differences so that they approach each difference satisfactorily to create a positive learning environment in their classrooms.